Jeruzalem – a co-existance of a traditional Catholic and New Age sacred place in Northeastern Slovenia - Kandrič Koval, Irena (Anali PAZU HD, 2022)
This article shows an example of the power of place in Northeastern Slovenia called Jeruzalem and it studies its nowadays, based on Gebhard Fartacek model, sacred pilgrimage place characteristics which have been appearing since the Middle Ages. It was given its name in 13th century by Teutonic Knights Templar on their return from Israeli Jerusalem. A legend speaks of a symbolic similarity to the Holy Land and Jerusalem they found out. Jeruzalem as a place of power provided a study linked to qualitative interviews and analysed as a social construction of space. The analysis showed nowadays Jeruzalem as a co-existance of diverse spiritualities (traditional Catholic and New Age) and it kept a status of a special ethnological/anthropological sacred place.